Are virtual anime endorsers a new type of endorser? Examining product involvement as a moderating role - Liang, Huai-Liang; Yang, Feng-Hua (Frontiers in Psychology, 2022)
Virtual anime endorsement has been prevalent as an advertising strategy, and many companies invest massive amounts of money into virtual endorsements. While previous studies have found that endorser-product congruence is related to consumer brand attitude and purchase intention, it is not known whether moderate incongruence between a virtual anime endorser and a product has a positive influence on brand attitude and purchase intention. This study developed a 1 × 2 experiment to investigate the influences of virtual anime endorser–product congruence and moderate the endorser–product incongruence on consumer brand attitude and purchase intention. Product involvement played a key moderating role in the relationships of virtual anime endorser–product congruence and the endorser–product incongruence with consumer attitudes. A total of 919 participants were recruited from animation-related venues and stores in Taiwan. The findings of this study validated the interaction effects of virtual anime endorser-product congruence and incongruence on these two consumer responses, i.e., brand attitude and purchase intention. This study further investigated the moderating effect of product involvement in the relationships of virtual anime endorser–product congruence and moderate the endorser–product incongruence with consumer responses. The findings of this study provide a valuable reference regarding endorsers and product patterns through which enterprises can maximize their value.